A iteratividade: do melodrama à narrativa audiovisual sob demanda - Affini, Leticia Passos [UNESP]; Cazani Júnior, Luis Enrique [UNESP] (My University, 2015)
The repetition should be understood as the property of mass cultural products, originated from the need to minimize the dispersion of the audience in their enjoyment. Based on this assumption, this paper measures the rate of iteration manifested in the scripts of the following serial fictions: Duas Caras, A Grande Família and House of Cards. Established itself as a method of scene analysis proposed by McKee (2008), questioned whether the lack of classical education of the public and rescued the forms assumed by repeating the melodrama, romance-serial and dramaturgy: asides, monologues, confidences and planar scenes. The proposal was applied in two scripts for each of the aforementioned productions. Considering the data collected, it appears that there was reduction in repeat products offered on demand thanks to the possibility of handling the flow and the attention given receptor.

Compreende-se repetição como uma propriedade dos produtos culturais, que se origina da necessidade de minimizar a dispersão da audiência durante a fruição. Partindo desse pressuposto, o presente trabalho mensura o índice de iteração manifestado nos roteiros das seguintes ficções seriadas: Duas Caras, A Grande Família e House of Cards. Como método, estabeleceu-se a análise de cena proposta por Mckee (2008), questionou-se o analfabetismo do público e resgataram-se as formas assumidas pela repetição no melodrama, no romance-folhetim e na dramaturgia: apartes, monólogos, confidências e cenas planas. A proposta foi aplicada em dois roteiros de cada uma das produções citadas. Considerando-se os dados levantados, conclui-se que há uma diminuição da repetição em produtos ofertados sob demanda, graças à possibilidade de manuseio do fluxo e à atenção dedicada do receptor.
Keywords: Audiovisual; Repetition; On demand; Audiovisual; Repetição; Sob demanda